Lip Forces and Chewing Efficiency in Children with Peripheral Facial Paralysis - Ilea, Aranka; Cristea, Alexandru; Dudescu, Cristian M.; Hurubeanu, Lucia; Vâjâean, Cosmin; Albu, Silviu; Câmpian, Radu S. (Neuropediatrics, 2015)
Peripheral facial paralysis is accompanied by facial motor disorders and also, by oral dysfunctions. The aim of this study was to evaluate the lip forces and chewing efficiency in a group of children with peripheral facial paralysis. The degree of peripheral facial paralysis in the study group (n = 11) was assessed using the House–Brackmann scale. The control group consisted of 21 children without facial nerve impairment. To assess lip forces, acrylic vestibular plates of three sizes were used: large (LVP), medium (MVP) and small (SVP). The lip force was recorded with a force transducer coupled with the data acquisition system. Masticatory efficiency was evaluated by the ability to mix two differently colored chewing gums. The images were processed with Adobe Photoshop CS3 (Delaware Corporation, San Jose, California, United States) and the number of pixels was quantified with the Image J software (DHHS/NIH/NIMH/RSB, Maryland, United States). For statistical analysis, the following statistical analysis were used: Pearson or Spearman correlation coefficient, multiple linear regression analysis, multiple logistic regression analysis, and optimal cutoff values for muscular dysfunction. There were statistically significant differences between lip forces in the following three groups: p = 0.01 (LVP), p = 0.01 (MVP), and p = 0.008 (SVP). The cutoff values of lip forces in the study group were as follows: 7.08 N (LVP), 4.89 N (MVP), and 4.24 N (SVP). There were no statistically significant differences between the masticatory efficiency in the two groups (p = 0.25). Lip forces were dependent on the degree of peripheral facial paralysis and age, but not on gender. In peripheral facial paralysis in children, a significant decrease of lip forces, but not masticatory efficiency, occurs.
Keywords: lip; measurement of lip force; mastication; chewing efficiency; facial paralysis; facial palsy